2017
DOI: 10.1007/s00127-017-1394-9
|View full text |Cite
|
Sign up to set email alerts
|

Do racial patterns in psychological distress shed light on the Black–White depression paradox? A systematic review

Abstract: A systematic review of the epidemiologic evidence supports the existence of a "double paradox" by which Blacks' lower prevalence of MDD relative to Whites' is inconsistent with both the expectations of social stress theory and with the empirical evidence regarding psychological distress. Efforts to resolve the Black-White depression paradox should account for the discordant distress results, which seem to favor artifactual explanations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
125
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(140 citation statements)
references
References 90 publications
10
125
3
2
Order By: Relevance
“…Once we take into account chronic stress exposure, blacks and whites report similar levels of anxiety and depressive symptomology. This is consistent with findings showing higher levels of psychological distress among blacks relative to whites and is in line with prior studies that show similar or lower rates of diagnosed or depressive and anxiety symptomology among blacks despite higher levels of stress exposure ( 12 ). Importantly, despite being exposed to more chronic stressors and reporting more anxiety and depressive symptoms, older blacks in this sample appraise exposure to chronic stressors as less upsetting than older whites.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Once we take into account chronic stress exposure, blacks and whites report similar levels of anxiety and depressive symptomology. This is consistent with findings showing higher levels of psychological distress among blacks relative to whites and is in line with prior studies that show similar or lower rates of diagnosed or depressive and anxiety symptomology among blacks despite higher levels of stress exposure ( 12 ). Importantly, despite being exposed to more chronic stressors and reporting more anxiety and depressive symptoms, older blacks in this sample appraise exposure to chronic stressors as less upsetting than older whites.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, for depressive symptoms, interactions between race and cumulative stress exposure show blacks reporting greater exposure to chronic stressors report fewer symptoms relative to whites with similar cumulative stress exposure. This finding aligns with studies examining the black–white mental health paradox which has primarily shown the black mental health advantage to be most evident for major depression ( 12 , 14 ). These studies have generally found that despite greater stress exposure, material hardship, and worse physical health, black Americans tend to experience similar or relatively lower rates of depression relative to whites ( 15 , 16 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Though previous studies confirm that rates of major depressive disorder (MDD) are lower for African Americans compared to Whites, some researchers have argued that psychiatric measures for depression may not be the most accurate assessment to use for African Americans [ 8 , 9 , 10 , 11 ]. Community-based studies frequently refer to other symptoms—not captured in psychiatric measures—that may reflect experiences of psychological distress more accurately, rather than depression, for some African Americans [ 12 ]. Though there has not been a comprehensive explanation for the cause and definition of psychological distress, researchers have made various attempts at understanding the term.…”
Section: Introductionmentioning
confidence: 99%